Quantification of the major bioactive phytochemicals in the gabiroba (Campomanesia xanthocarpa Berg) juice - doi: 10.4025/actascitechnol.v35i4.13910 - Marli da Silva Santos; Carlos Henrique Correia; Carmen Lucia de Oliveira Petkowicz; Lys Mary Bileski Cândido (Acta Scientiarum: Technology, 2013)
The juice was evaluated regarding yield, turbidity, physicochemical characteristics and acceptability. In order to check the acceptability, three samples were prepared by adding sucrose until reaching 12, 14 and 16°Brix, respectively, once this is the characteristic range of commercial samples for ready-made juices. The use of enzymes increased the juice yield, which showed a good retention of bioactive compounds. The sample with the highest overall acceptance was that of 14°Brix with a overall average of eight, corresponding to the expression ‘I liked it very much’, suggesting a high market potential.